2017
DOI: 10.1515/jos-2017-0049
|View full text |Cite
|
Sign up to set email alerts
|

Figuring Figures: Exploring Europeans’ Knowledge of Official Economic Statistics

Abstract: Economic issues have been a major concern for Europeans in the last few years. In this context, it is reasonable to suppose that people are aware of the main economic figures regarding Europe. But are they really familiar with them? Do they know what the rates of growth, unemployment and inflation are?The aim of this article is to explore the level of knowledge of these three economic indicators among Europeans. Several regression models are specified and estimated in order to identify the relationship between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Earlier studies from Germany (Mohr et al 2014 ) and Italy (Fullone et al 2008 ) had come to similar conclusions. Pan-European studies also show significant cross-country differences (Papacostas 2008 ; Vicente and López 2017 ), some of which may be attributed to socio-economic differences between countries (e.g. different average levels of education) or national economic conditions.…”
Section: The Relevance Of Economic Knowledge For Democratic Politicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Earlier studies from Germany (Mohr et al 2014 ) and Italy (Fullone et al 2008 ) had come to similar conclusions. Pan-European studies also show significant cross-country differences (Papacostas 2008 ; Vicente and López 2017 ), some of which may be attributed to socio-economic differences between countries (e.g. different average levels of education) or national economic conditions.…”
Section: The Relevance Of Economic Knowledge For Democratic Politicsmentioning
confidence: 99%
“…Our empirical analysis uses two Eurobarometer (EB) waves, with respondent-level information that we use to proxy key explanatory variables. Vicente and López ( 2017 ) have analyzed differences in economic knowledge using one of the EB waves (2015) that we analyze as well. Although many of our variables coincide with theirs, their analysis is less theory-driven and more focused on cross-country differences, uses a different specification, and does not include the earlier EB wave (which we leverage to compare pre-Eurozone crisis to post-crisis levels of public economic knowledge, cf.…”
Section: Hypotheses and Observable Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have suggested that the public tends to identify internal economic crises that a country may undergo ( Berry & McDaniel, 2022 ), specially university students when the crises directly affect their job market prospects ( Chen & Yur-Austin, 2016 ). However, this judgment largely correlates with economic knowledge, which varies across socio-demographic cohorts ( Vicente & López, 2017 ). In that sense, we consider it pertinent to explore university students’ economic perceptions and opinions regarding an external conflict that, prima facie , has nothing to do with their homeland and analyze whether these preconceptions are reflected in their responses.…”
Section: Introductionmentioning
confidence: 99%